COVID-19 vaccine demand, hesitancy, and nationalism: a case of protection motivation behavior in Bangladesh - Mostafizur Rahman; Afnan Hossain; Abu Sufian; Nahida Anwar (Journal of Infection in Developing Countries)
Introduction: Immunization, as a process of fighting against the COVID-19, has gained important research appeal, but very limited endeavor has been paid for vaccine behavioral studies in underdeveloped and developing countries. This study explores the vaccine demand, hesitancy, and nationalism as well as vaccine acceptance and domestic vaccine preference among young adults in Bangladesh.